Articulation Time Does Not Affect Speeded Cognitive Performance in Multiple Sclerosis. Issue 1 (March 2015) - Roberg, Brandon Lars; Somogie, Melanie; Thelen, Joanie M.; Bruce, Jared M.
<x xml:space="preserve">Abstract</x> Objective and Background: Cognitive test performance by individuals with multiple sclerosis (MS) may be biased because of MS-related speech problems. The purpose of this study was to compare articulation and pause durations between individuals with MS and controls on cognitive tests requiring an oral response. Method: As part of a neuropsychological assessment, 41 patients with MS and 23 controls completed oral forms of 2 timed cognitive tests that are commonly used in MS. Acoustic analysis software segmented oral test responses into "articulation" and "pause" time durations. Results: Overall cognitive test performance by the patients with MS was significantly associated with average pause duration, but not average articulation duration. Articulation time did not contribute to or confound the outcome of either test. Conclusions: Articulation time did not contribute to differences in test performance between patients with MS and controls; rather, the time spent in silence between responses (pause time) largely accounted for group differences. Future research could use the methods described here to study speech characteristics during cognitive tests that require oral responses for patients with known speech impairments and more progressive forms of MS.